Edukasi Penanganan Pertama Dengan Pemanfaatan Tanaman Obat Untuk Pencegahan Dan Penanggulangan Hipertensi di Puskesmas Maccini Sawah - Nurhayati Nurhayati; Basmalah Harun; Yantimala Mahmud; Andina Andina; Haslinda Haslinda (Jurnal DIKMAS, 2025)
The prevalence of hypertension in Indonesia in 2020 is 31.7% of the population aged 18 years and over. Around 80% of people with hypertension are classified as essential hypertension. Blood pressure in hypertensive sufferers can be lowered pharmacologically and non-pharmacologically. Pharmacological reduction can be done by taking drugs recommended to lower blood pressure. Non-pharmacologically, you can reduce blood pressure by modifying your lifestyle and consuming medicinal plants. Medicinal plants can be used as alternative medicines for the prevention and control of hypertension which do not have side effects, are cheap and easy to obtain because they can be cultivated yourself. The aim of this community service is to provide education about the benefits of medicinal plants for first aid for minor health problems through traditional medicine which has the potential to treat and prevent hypertension. The service method carried out consists of two stages, namely counseling and planting traditional medicinal plants. This activity was attended by 20 participants. From the results of the evaluation and discussion, participants enthusiastically asked about herbs around their homes and people were willing to plant herbs in their yards.